A Jamaican Response to the Call to Act Together: "For the Love of Christ Urges Us On” (2 Cor. 5:14) - Vernon, Evie (International review of mission, 2023)
This article is an exploration of following the way of Jesus regarding apologies and restitution for slavery. Three stories of good practice from the North American Jesuits, the United Reformed Church, and the Church of England are contrasted with stories of the abuse of children from First Nations people in Canada, poor families in Ireland, and the transportation of allegedly indigent children from Britain to Australia. These accounts are used to examine critically how far the church is following the call of Jesus to care for the vulnerable and identify with the marginalized in interactions with those sexually abused in churches, in engagement with sex workers, and the treatment of the LGBTQ+ community. A poetic reflection from the voice of the man who lived outside his community of the Gadarenes concludes the article.